MCKUSIK KAUFMAN SYNDROME - Malik, Faisal Raza; Tahir, Awais; Bashir, Huma (Journal of Ayub Medical College Abbottabad, 2012)
A 12-years-old male child presented with polydactyly and syndactyly of hands, hypospadias, AND undescended testes. He was a known case of Tetrology of Fallot. One important differential in our case was Bardet-Biedl syndrome, but it was ruled out due to lack of evidence of central obesity, mental retardation and retinitis pigmentosa. At this time, there is no molecular testing available to distinguish these two syndromes. Keywords: Mckusik Kaufman syndrome, polydactyly, syndactyly, hypospadias